2015
DOI: 10.1002/ange.201411234
|View full text |Cite
|
Sign up to set email alerts
|

The Fluorenyl Cation

Abstract: The fluorenyl cation is a textbook example for a 4π antiaromatic cation. However, contrasting results have been published on how the annelated benzene rings compensate the destabilizing effect of the 4π antiaromatic five‐membered ring in its core. Whereas previous attempts to synthesize this cation in superacidic media resulted in undefined polymeric material only, we herein report that it can be generated and isolated in amorphous water ice at temperatures below 30 K by photolysis of diazofluorene. Under thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…A similar investigation of the interaction of fluorenylidene with water demonstrated strong hydrogen bond formation with the singlet, but only a weak interaction with the triplet. 18 Additional studies of chloro-and fluorophenylcarbenes at the B3LYP-D3/6-311++G(2d,2p) level of theory obtained hydrogen-bonded complexes between the singlet carbenes and water with binding energies of around −7 kcal/mol and singlet−triplet gap reversal similar to that found in the previous work. 19 Though some specific cases have been studied recently, 16−19 the formation of hydrogen bonds involving singlet and triplet carbenes has not received a great deal of attention.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…A similar investigation of the interaction of fluorenylidene with water demonstrated strong hydrogen bond formation with the singlet, but only a weak interaction with the triplet. 18 Additional studies of chloro-and fluorophenylcarbenes at the B3LYP-D3/6-311++G(2d,2p) level of theory obtained hydrogen-bonded complexes between the singlet carbenes and water with binding energies of around −7 kcal/mol and singlet−triplet gap reversal similar to that found in the previous work. 19 Though some specific cases have been studied recently, 16−19 the formation of hydrogen bonds involving singlet and triplet carbenes has not received a great deal of attention.…”
Section: Introductionsupporting
confidence: 78%
“…A third related study explored the hydrogen-bonding interaction of singlet fluorenylidene with water, which forms a strong hydrogen-bonded complex and then is protonated by water to produce the fluorenyl cation. 18 Finally, singlet chloro-and fluorophenylcarbene have been shown to interact via hydrogen bonding with water in argon matrixes at low temperature to form complexes which lead to stabilization of the singlet carbene and switching of the ground state. 19 There have been a few other recent attempts to control the spin state of carbenes using methods other than hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%
“…The singlet states of nitrenes are also stabilized when the nitrene center is attached to heteroatoms such as transition metals (metal− nitrido complexes), nitrogen (aminonitrenes), or phosphorus (phosphinonitrenes). 29 Recently, we demonstrated that the closed-shell singlet states of arylcarbenes such as diphenylcarbene 9 can be stabilized by interactions with Lewis acids such as water, 30,31 methanol, 32,33 CF 3 I, 34 or BF 3 . 35 Thus, while the triplet ground state of diphenylcarbene T-9 lies approximately 5 kcal/mol below the closed-shell singlet state S-9, the singlet state becomes a ground state upon interaction with a single molecule of water or methanol.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, we demonstrated that the closed-shell singlet states of arylcarbenes such as diphenylcarbene 9 can be stabilized by interactions with Lewis acids such as water, [30][31] methanol, [32][33] CF3I, 34 or BF3. 35 Thus, while the triplet ground state of diphenylcarbene T-9 lies approximately 5 kcal/mol below the closed-shell singlet state S-9, the singlet state becomes ground state upon interaction with a single molecule of water or methanol.…”
mentioning
confidence: 99%
“…26,27 Recently, we reported a new technique for the matrix isolation of the benzhydryl cation 2a and the fluorenyl cation 2e by protonation of the corresponding carbenes 3 and 4, respectively, in LDA ice (Scheme 4). 28,29 The singlet states of carbenes 3 and 4 are very strong, neutral bases that even at extremely low temperatures (3 K) are rapidly protonated by water molecules to produce OH − and the cations 2a and 2e, respectively. The hydroxide ion is efficiently stabilized in the hydrogen-bond network of the water matrix, and recombination with the cations to form the corresponding alcohols is inhibited.…”
Section: ■ Introductionmentioning
confidence: 99%